Nutrient absorption by Marandu grass subjected to shading levels and nitrogen doses in a silvopastoral system - Josiane Aparecida de Souza Barboza; Márcia Vitória Santos; Francisco Cláudio Lopes de Freitas; Paulo Roberto Cecon; Rodinei Facco Pegoraro; Arnon Henrique Campos Anésio; Herminia Emilia Prieto Martinez; Mariana Almeida Dumont (Semina: Ciências Agrárias)
The objective was to evaluate nutrient absorption in Marandu grass influenced by levels of eucalyptus shading in a silvopastoral system (SSP) and N doses, during two years of cultivation. The experimental design adopted was randomized blocks, with four replications. The experiment was conducted in a 3 x 7 factorial arrangement, corresponding to three nitrogen doses (0, 100, and 200 kg ha-1 year-1 in the form of ammonium sulfate), six shading intensities of Marandu grass in SSP (SSP 40-45, SSP 35-40, SSP 30-35, SSP 25-30, SSP 20-25, SSP 15-20%), and one treatment with Marandu grass cultivated in full sun (monoculture). Chemical analyzes were performed to obtain macro and micronutrient concentrations in the Marandu grass material. The adoption of the integrated SSP system and N doses showed interaction (P <0.05) for phosphorus (P), potassium (K), and sulfur (S) levels in Marandu grass. Shading does not affect the dry mass production of Marandu grass. The increase in N doses and shading in the SSP favor the levels of phosphorus, potassium, sulfur, nitrogen, calcium, magnesium, iron, zinc, copper, manganese and boron in Marandu grass, compared to full sun. The presence of 40-45% shade provides the highest levels, demonstrating greater benefits for forage quality in SSPs compared to monoculture pastures.